PENGGUNAAN FRASA BAHASA INDONESIA DALAM KARANGAN SISWA KELAS VII MTsN RENGEL TAHUN PELAJARAN 2014/2015 - Rahman, Minanur (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2015)
This study aimed (1) to describe the form of the noun that became a core element, (2) the type of words to attributive element, (3) pattern, and (4), function occupied Indonesian noun phrases in the essay. This study was designed using qualitative descriptive approach. The data for this study were the nouns found in the students’ essay. While the source of the data in this study were students’ essay of class VII MTsN Rengel in 2014/2015 academic year. In gathering the data the researcher used two techniques: the testing and recording technique. From result of the study, the researcher found that: (1) the three forms of the noun that became a core element were noun phrases: noun form of the base and noun derivative form; (2) Type a word into the attributive element to the Indonesian noun phrase consists of five kinds: (a) nouns, (b) verb, (c) an adjective, (d) the word number, and (e) pronouns; (3) The pattern of Indonesian noun phrase consists of two things: (a) the pattern of DM and (b) the pattern of MD; and (4) functions element occupied Indonesian noun phrase consists of four functions: (a) the subject, (b) predicate, (c) the object, and (d) complementary.